ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA MODAL INTELEKTUAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuliarti, Norita Citra (Universitas Muhammadiyah Jember, 2017)
Abstract: The purpose of this study was to determine the extent of Intellectual Capital voluntary disclosure in the annual report of mining firm listed on the stock exchange Indonesia 2011-2013. The objective of this study was to analyze the influence of managerial ownership, frequencies of audit committee?s meeting, research and development, age of company as the independent variabel to extent of intellectual capital voluntary disclosure. Content analysis method was used as data collection techniques to examine the extent of intellectual capital voluntary in the firm annual report. The sample used in this research was annual reports all of company listed at Indonesia Stock Exchange. Samples were selected with purposive sampling technique that is with criteria mining company listed on the Indonesian Stock Exchange, Publish the full annual report in 2011-2013. The sample used was of 35 firms. The statistics method used was multiplied analysis linear regression, with hypotheses testing of statistic t and F tests at the level of 5%. Research and development and age of company significant influence on extent of intellectual capital voluntary disclosure.Keyword: Annual Report, Intellectual Capital, Managerial Ownership, Voluntary Disclosure